Solar Water Splitting and Nitrogen Fixation with Layered Bismuth Oxyhalides - Li, Jie; Li, Hao; Zhan, Guangming; Zhang, Lizhi (Accounts of chemical research, 2017)
Hydrogen and ammonia are the chemical molecules that are vital to Earth’s energy, environmental, and biological processes. Hydrogen with renewable, carbon-free, and high combustion-enthalpy hallmarks lays the foundation of next-generation energy source, while ammonia furnishes the building blocks of fertilizers and proteins to sustain the lives of plants and organisms. Such merits fascinate worldwide scientists in developing viable strategies to produce hydrogen and ammonia. Currently, at the forefronts of hydrogen and ammonia syntheses are solar water splitting and nitrogen fixation, because they go beyond the high temperature and pressure requirements of methane stream reforming and Haber–Bosch reaction, respectively, as the commercialized hydrogen and ammonia production routes, and inherit the natural photosynthesis virtues that are green and sustainable and operate at room temperature and atmospheric pressure. The key to propelling such photochemical reactions lies in searching photocatalysts that enable water splitting into hydrogen and nitrogen fixation to make ammonia efficiently. Although the past 40 years have witnessed significant breakthroughs using the most widely studied TiO2, SrTiO3, (Ga1–x Zn x )(N1–x O x ), CdS, and g-C3N4 for solar chemical synthesis, two crucial yet still unsolved issues challenge their further progress toward robust solar water splitting and nitrogen fixation, including the inefficient steering of electron transportation from the bulk to the surface and the difficulty of activating the NN triple bond of N2. This Account details our endeavors that leverage layered bismuth oxyhalides as photocatalysts for efficient solar water splitting and nitrogen fixation, with a focus on addressing the above two problems. We first demonstrate that the layered structures of bismuth oxyhalides can stimulate an internal electric field (IEF) that is capable of efficiently separating electrons and holes after their formation and of precisely channeling their migration from the bulk to the surface along the different directions, thus enabling more electrons to reach the surface for water splitting and nitrogen fixation. Simultaneously, their oxygen termination feature and the strain differences between interlayers and intralayers render the easy generation of surface oxygen vacancies (OVs) that afford Lewis-base and unsaturated-unsaturated sites for nitrogen activation. With these rationales as the guideline, we can obtain striking visible-light hydrogen- and ammonia-evolving rates without using any noble-metal cocatalysts. Then we show how to utilize IEF and OV based strategies to improve the solar water splitting and nitrogen fixation performances of bismuth oxyhalide photocatalysts. Finally, we highlight the challenges remaining in using bismuth oxyhalides for solar hydrogen and ammonia syntheses, and the prospect of further development of this research field. We believe that our mechanistic insights could serve as a blueprint for the design of more efficient solar water splitting and nitrogen fixation systems, and layered bismuth oxyhalides might open up new photocatalyst paradigm for such two solar chemical syntheses.